2014
DOI: 10.1016/j.jtcvs.2014.05.090
|View full text |Cite
|
Sign up to set email alerts
|

Is single-dose prophylactic gentamicin associated with acute kidney injury in patients undergoing cardiac surgery? A matched-pair analysis

Abstract: A single-dose prophylactic aminoglycoside in adult cardiac surgery patients was associated with an increased risk of acute kidney injury but not with a greater frequency of postoperative dialysis or mortality. No differences in the incidence of sternal infections between groups were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
(33 reference statements)
0
18
0
2
Order By: Relevance
“…Thirty‐six studies were included in the final synthesis: one thesis and 35 journal articles . The 36 studies included 11 randomized controlled studies (two crossover designs), 18 cohort studies, one retrospective survey, three pharmacokinetic and three quasiexperimental studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐six studies were included in the final synthesis: one thesis and 35 journal articles . The 36 studies included 11 randomized controlled studies (two crossover designs), 18 cohort studies, one retrospective survey, three pharmacokinetic and three quasiexperimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…Reported adverse events are summarized in Table . Twenty‐three , of the 36 included studies, reported adverse events in the gentamicin arm of their study although not all adverse events were related to gentamicin. Pons et al .…”
Section: Resultsmentioning
confidence: 99%
“…Niesel et al, also noted AKI with rise in serum creatinine in 22% cases after receiving single prophylactic dose of gentamycin [12].…”
Section: Resultsmentioning
confidence: 93%
“…We also assessed the incidence of AKI with the Acute Kidney Injury Network and the KDIGO definitions, and we did not identify any new case of AKI using these definitions. Finally, we chose to include patients who received at least 5 days of AG since when we designed the study, there were no published data on the possible nephrotoxicity associated with a single dose of AG [10,49]. We do not know whether our results apply to patients receiving empiric AG treatment for a few days until culture results become available.…”
Section: Discussionmentioning
confidence: 99%